2018
DOI: 10.3390/molecules23092110
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-Friendly Extraction of Flavonoids from Cyclocarya paliurus (Batal.) Iljinskaja Leaves with Deep Eutectic Solvents and Evaluation of Their Antioxidant Activities

Abstract: Deep eutectic solvents (DESs) are commonly employed as environmentally-friendly solvents in numerous chemical applications owing to their unique physicochemical properties. In this study, a novel and environmentally-friendly extraction method based on ultrasound assisted-deep eutectic solvent extraction (UAE-DES) was investigated for the extraction of flavonoids from Cyclocarya paliurus (Batal.) Iljinskaja (C. paliurus) leaves, and the antioxidant activities of these flavonoids were evaluated. Nine different D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 39 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…The traditional extraction processes using organic solvents often induces toxicity and involves the use of flammable, explosive, and poorly biodegradable substances. Therefore, it is necessary to find a green extraction technology for such purposes [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional extraction processes using organic solvents often induces toxicity and involves the use of flammable, explosive, and poorly biodegradable substances. Therefore, it is necessary to find a green extraction technology for such purposes [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, extraction and separation of flavonoids from C. paliurus using a traditional method with organic solvent and chromatography, which brings derivative problems such as waste of labor, consumption of resource, harm to human health and environmental pollution etc. Environment‐friendly methods with new technique were investigated recently years, including ultrasound assisted‐deep eutectic solvent extraction (UAE‐DES) (Shang, Tan, Du, Liu, & Zhang, 2018 and microwave irradiation (Xie et al, 2015). Aqueous two‐phase system (ATPS) is a new liquid‐liquid fraction technique that has been extensively applied in the separation and purification of natural products including phenols (Xu, Qiu, Ren, Ju, & Jia, 2017), flavonoids (He, Li, Wang, & Deng, 2016), alkloid (Zhou et al, 2018), proteins (Chang, Show, Lan, Tsai, & Huang, 2018), genetic material (Nazer, Dehghani, & Goliaei, 2017), polysaccharide (Li et al, 2017)and secondary metabolites etc.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) has been applied for process optimization (Liu, 2012; Yang et al, 2007). RSM is a collection of statistical techniques and mathematical models that are used to define the relationship between the variables and the response (Shang et al, 2018). RSM is use of developin.g, improving and optimizing processes as well as is used to examine the relationship between one or more response variables and a set of quantitative experimental variables or factors.…”
Section: Introductionmentioning
confidence: 99%
“…The tailor-made DESs have tremendous potential for efficient and simultaneous extraction and separation of compounds which have obvious differences in nature [16]. Recently, many reports have shown that tailor-made DESs were successfully employed in the extraction and separation of different kinds of bioactive compounds, such as phenolic acids, flavonoids, alkaloids, and saponins, from various plant materials [17,18,19,20,21,22]. Nonetheless, most of the research used tailor-made binary DESs as extraction solvents for bioactive compound extractions, the number of reports on the application of tailor-made ternary DESs for extraction is still limited, and the efficiency of DESs for extraction of bioactive phenolic acids from AL still remains unknown.…”
Section: Introductionmentioning
confidence: 99%